Etika Guru Terhadap Murid Menurut Perspektif Al-Qur’an Serta Relevansinya Dengan Konsep Pendidikan Modern - Syafawi, Qamar; Asraddin (LPPM Universitas Almuslim, 2024)
This research aims to describe teacher ethics towards students from the perspective of the Qur'an and its relevance to modern educational concepts. The verses used are Surah Ali Imran Ayat 159 and Surah Ar-Rahman Ayat 1-4. The method employed in this research is a qualitative research method with a thematic interpretation (tafsir maudhu’i) approach. The analysis used is content analysis, which aims to analyze the verses related to teacher ethics towards students. Surah Ali Imran Ayat 159. The ethics of teachers towards students in Surah Ali Imran Ayat 159 include: Teachers should be gentle towards their students, they should not be harsh and hard-hearted, they should easily forgive the mistakes of their students, they should pray for and seek forgiveness from Allah for their students, they should engage in consultation when making joint decisions, they should place their trust in Allah for all their actions. and surah ar-Rahman Ayat 1-4 The ethics of teachers towards students in Surah Ar-Rahman Ayat 1-4 include: Teachers should be compassionate towards all their students, they should be capable and proficient in teaching the Qur'an and other sciences without neglecting the Qur'an as the foundation, teachers should strive to shape students into complete human beings. they should be able to explain lessons well and provide a clear understanding of the subjects taught. Relevance to Modern Educational Concepts these values are highly relevant to the principles of modern education, which emphasize the importance of a supportive, inclusive, and student-centered learning environment